ORAL HEALTH OF YOUNG INDIVIDUALS WITH DISABILITIES, AN INDICATOR FOR THE QUALITY OF LIFE - Mirel Șipoteanu; Liliana Foia; Iulia-Cătălina Săveanu; Alice Murariu; Simina Vacariu; Alina Adumitroaie; Daniel Cioloca; Cosmin Gabriel Tartău; Andreea Ciucă; Vasilica Toma (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study Disability does not annul the right of an individual to receive qualitative health care, which includes oral and dental care; instead, it should actually increase the attentiveness of caregivers and medical providers regarding oral hygiene and treatment measures, considering the high risks of this category of population. Especially in the case of children and adolescents, population with a high prevalence of different types of disabilities, oral and dental care is often disregarded. This study aims to review current information in literature referring to disabled children and adolescents and the management of oral and dental care in the context of their quality of life. Material and methods A literature review was performed, after evaluating recent articles and studies, using the search terms: children, adolescents, disability, dental care. Results Inclusion of disabled individuals and their integration in society is more and more present, leading to concern regarding healthcare needs in general, and oral and dental care needs in particular. Since children and adolescents with disabilities present a greater risk for dental caries and periodontal pathology, efforts are made to prevent and properly manage these conditions. Conclusions Special needs dentistry benefits from the incredible evolution of social perception on disability, as well as technological and medical development available. Nevertheless, in our country, oral healthcare and dental prevention programs aimed at children and adolescents with disability are scarce, underlying an urgent need to develop and implement national strategies and plans to fulfil the worldwide current objective of a caries-free population.